2007
DOI: 10.1038/sj.jes.7500552
|View full text |Cite
|
Sign up to set email alerts
|

Source location of air pollution and cardiac autonomic function: Trajectory cluster analysis for exposure assessment

Abstract: Although many studies report that exposure to air pollution harms health, few have examined associations between pollution sources and health outcomes. We hypothesized that pollution originating in different locations has different associations with heart rate variability (HRV) among 497 men from the Normative Aging Study in Boston, Massachusetts. We identified the paths that air masses traveled ('back-trajectories') before arriving in Boston on the days the men were examined. Next, we classified these traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…In Boston, BC is a marker of traffic particles influenced by both local traffic, with a morning peak, and long-range transported traffic particles (Park et al 2007). NO 2 , a lower-airway irritant, is mainly a secondary pollutant, which in Boston mostly originates from traffic and regional sources including power plants and vehicular emissions (Rattigan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Boston, BC is a marker of traffic particles influenced by both local traffic, with a morning peak, and long-range transported traffic particles (Park et al 2007). NO 2 , a lower-airway irritant, is mainly a secondary pollutant, which in Boston mostly originates from traffic and regional sources including power plants and vehicular emissions (Rattigan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that pollutant mixtures, as indexed by air masses with specific back trajectories, influence the health effects of particles (Park et al 2007). Specifically, the authors identified the paths that air masses traveled (‘back-trajectories’) before arriving in Boston, and they classified these trajectories into six clusters.…”
Section: Discussionmentioning
confidence: 99%
“…One parameter used to assess this regulation is HRV; reduction in HRV is associated with increased risk of CV morbidity and mortality in both healthy individuals and patients following MI (Tsuji et al, 1996;Kleiger et al, 1987). Studies finding associations between BC and reduced HRV, often in older or chronically ill subjects, include Suh and Zanobetti (2010), Schwartz et al (2005a), Adar et al (2007), Wheeler et al (2006), and Park et al (2007. However, studies examining HRV in normal subjects, and even in an at-risk population with stable coronary heart disease, exposed to DEE showed no reproducible or consistent changes in HRV related to exposure (Peretz et al, 2008;Mills et al, 2011).…”
Section: Cardiovascular Morbidity-human Panel Studiesmentioning
confidence: 99%
“…It is surprising that poor exposure assessment did not cause BC associations to become insignificant in more studies than it did. Many of these studies commented that there was greater exposure misclassification for BC than for other pollutants (Chuang et al, 2008) and that poor subject exposure to BC should have attenuated BC associations or biased them toward the null, but did not (Bind et al, 2012;Baja et al, 2010;Baccarelli et al, 2009;O'Neill et al, 2007). Goldman et al (2010) estimated error in risk estimates due to spatial variability not accounted for when central monitor data were used as a proxy for subject exposure.…”
Section: Syntheses Of Findings From Studies In North America and Westmentioning
confidence: 99%